2017
DOI: 10.19082/5974
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy rule-based expert system for diagnosing cystic fibrosis

Abstract: BackgroundFinding a valid diagnosis is mostly a prolonged process. Current advances in the sector of artificial intelligence have led to the appearance of expert systems that enrich the experiences and capabilities of doctors for making decisions for their patients.ObjectiveThe objective of this research was developing a fuzzy expert system for diagnosing Cystic Fibrosis (CF).MethodsDefining the risk factors and then, designing the fuzzy expert system for diagnosis of CF were carried out in this cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In spite of the emphasis in the clinical guidelines on the early detection of cardiac arrest and immediate intervention by the CPR team [1,13,14], unfortunately, there have been very few studies conducted on the arrival time of physician and resuscitation team and its association with the outcome of resuscitation. Therefore, this study was conducted with the objective of evaluating the arrival time of physician and resuscitation team at Imam Reza Hospital of Kermanshah in Iran during 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the emphasis in the clinical guidelines on the early detection of cardiac arrest and immediate intervention by the CPR team [1,13,14], unfortunately, there have been very few studies conducted on the arrival time of physician and resuscitation team and its association with the outcome of resuscitation. Therefore, this study was conducted with the objective of evaluating the arrival time of physician and resuscitation team at Imam Reza Hospital of Kermanshah in Iran during 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the diseases under study, an important variability in the number of targeted diseases was identified. The most individually studied diseases were thalassemia [20,28,29,47], Down syndrome [21,30,34], cystic fibrosis [46,48,52], Marfan syndrome [25,27] and Huntington disease [19,33].…”
Section: Publication Targetmentioning
confidence: 99%
“…The protocol to evaluate and validate the developed models was highly study-dependent and is detailed in the next subsections. The following characteristics were considered: Hybrid (7 studies) Yes [27,[73][74][75][76]78] No [25] Data driven (1 study) Yes [72] Fluids (12 studies) Hybrid (2 studies) Yes [28,29] Data driven (10 studies) Yes [20,23,24,31,36,42,47,48,56,60] Images (16 studies) Hybrid (2 studies) Yes [41,45] Data driven (14 studies) Yes [19, 21, 22, 30, 33-35, 43, 44, 49, 51, 57, 59, 62] Questionnaires (3 studies) Data driven (3 studies) Yes [52,53,58] Family history and combined material (8 studies) Knowledge-based (5 studies) No [26,32,38,46,50] Hybrid (2 studies) Yes [37,39] Data driven (1 study) Yes [40] References are listed in column "articles" according to the type of material considered and the model used (presence/absence of prior knowledge and of machine learning). The number of studies according to material and knowledge is given in parentheses Fig.…”
Section: Evaluation and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic fibrosis (CF) patients often have respiratory tract infections and bacterial colonization that require antibiotic therapy. Pseudomonas infection and a number of previous admissions have shown to be the major predictors of mortality in CF (2)(3)(4). The most common organisms causing respiratory infections in CF patients are pseudomonas aeruginosa, staphylococcus aureus, and stenotrophomonas maltophilia (5).…”
Section: Introductionmentioning
confidence: 99%